Political Communication Gaps in Palembang’s Smart City: Barriers to Policy Dissemination - Mahriadi, Nopriawan; Ardiansyah, Arif; Aryani, Desi; Ardiansyah, Ardiansyah; Santoso, Budi (PT Publikasiku Academic Solution, 2026)
Background: Smart City initiatives in developing countries often emerge as important responses to the challenges of urbanization, but often fail due to communication barriers specifically, policies that are not understood or engaged by the public. This study argues that a key barrier lies in the communication gap between policymakers and the public, with a focus on the Smart City initiative in Palembang. The study aims to investigate how the lack of clear policy communication and limited public engagement hinder these initiatives. Methods: This study analyzed policy documents using a qualitative approach, emphasizing the communication gap. Results: The main findings are that problems in communication flow, clarity, and consistency, particularly in vertical communication within government, and the lack of government digital outreach at the sub-district level, prevent effective public feedback and social adoption of smart technologies. Conclusions: This study highlights that a core challenge hindering Smart City projects in the developing country context is inadequate communication, which hinders public understanding and policy feedback. This study serves as a foundation for city governments, policymakers, and public administration professionals to develop more inclusive communication strategies, promote digital literacy, and foster responsive governance.